Host quality in the development cycle of Battus polydamas (Lepidoptera: Papilionidae: Troidini) - FAGUA, GIOVANNY; RUIZ, NATALIA; GONZÁLEZ, FAVIO; ANDRADE-C., MIGUEL GONZALO (Revista Colombiana de Entomología, 1998)
The selection of a host is an important factor affecting the probability of survival of an herbivore. Its influence is greater on highly monophagous guests. Battus polvdamas is an oligophagous herbivore on 24 species of Aristolochia, a toxic plant, and frequent Troidini host. A large number of host species suggest that many species of Aristolochia are suitable as hosts and do not significantly affect the survival probabilities of their guests. We examined two questions: Does B. polydatnas exhibit a preference for host species? and What effect does the host have on butterfly development? We studied oviposition and herbivory by B. polvdamas on eight species of Aristolochia. All species of Aristolochia were natural hosts, but there were significant differences between A ristolochia species with respect to the number of clusters laid. The butterflies preferred the apical zone for laying eggs. We measured host preference of eight species ofAristolochia by measuring leal areas for those portions that had been consumed; leaves were administered simultaneously to different caterpillar groups (caterpillars for each group were from different clutches). Leaf nutritional quality was measured by the growth and development of caterpillar groups fed on a single specie of Aristolochia. We didn ’t observe significant differences between consumption rates of leaves, but the caterpillars attained the pupae stage on only three species of A ristolochia . Caterpillar development was faster in the host with lower sclerophyll. We observed a close relation between sclerophyll levels and oviposition and herbivory preferences, but that wasn’t the only determining factor. Hosts don’t offer an equal survival possibility. Female butterflies could use a sub-optima( host when an ideal one wasn’t present; they do deposit their eggs on flowers or young leaves. We concluded that female butterflies exhibit preferences for species of Aristolochia that provided higher survival probabilities.